2015
DOI: 10.1002/app.41878
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of novel trifunctional epoxy triglycidyl of 4‐(4‐aminophenoxy)phenol with high toughness

Abstract: A trifunctional epoxy containing oxyphenylene unit, triglycidyl of 4-(4-aminophenoxy)phenol (TGAPP) was synthesized and characterized. The chemical structure of TGAPP was confirmed with FTIR and 1 H-NMR. DSC analysis revealed that the reactivity of TGAPP with curing agent 4, 4 0 -diaminodiphenylsulfone (DDS) was significantly lower than that of triglycidyl paraaminophenol (TGPAP). Rheological analysis showed that the processing window of TGAPP/DDS was 20 C wider compared with that of TGPAP/DDS. The thermal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…48 Toughness and stiffness enhancement resulting from the synergistic effect of the rigid aromatic rings and the flexible ether linkages in the epoxy backbone were also reported and found to have not compromised the thermal and mechanical properties of thermosets; paving the way for synthesis of monomers containing such modifications. 49,50 The effect of crystalline domains in the polymer chains as well as the effect of liquid crystal mesogens in the backbone of polymers also showed improvements in toughness and on other mechanical properties in epoxy resins. 51,52 In categorizing different ways of toughening epoxy resins, the succeeding approaches can fall in any of the following categories: (1) in sub-atomic level (modifying the molecules and using additives or micelles), (2) atomic level (crystalline structures and short-range vs. long-range order), and (3) microscopic level (introducing fibers to make isotropic vs. anisotropic composites).…”
Section: Toughness Enhanced Resinsmentioning
confidence: 99%
“…48 Toughness and stiffness enhancement resulting from the synergistic effect of the rigid aromatic rings and the flexible ether linkages in the epoxy backbone were also reported and found to have not compromised the thermal and mechanical properties of thermosets; paving the way for synthesis of monomers containing such modifications. 49,50 The effect of crystalline domains in the polymer chains as well as the effect of liquid crystal mesogens in the backbone of polymers also showed improvements in toughness and on other mechanical properties in epoxy resins. 51,52 In categorizing different ways of toughening epoxy resins, the succeeding approaches can fall in any of the following categories: (1) in sub-atomic level (modifying the molecules and using additives or micelles), (2) atomic level (crystalline structures and short-range vs. long-range order), and (3) microscopic level (introducing fibers to make isotropic vs. anisotropic composites).…”
Section: Toughness Enhanced Resinsmentioning
confidence: 99%
“…Unfortunately, because epoxy resins have a high crosslinking density, their toughness is lowered due to their hard and rigid composition 7 . This results in low fracture toughness, crack propagation, impact resistance, and elongation characteristics, which are fatal disadvantages 8 …”
Section: Introductionmentioning
confidence: 99%
“…7 This results in low fracture toughness, crack propagation, impact resistance, and elongation characteristics, which are fatal disadvantages. 8 Over the past few decades, the addition of toughening agents to epoxy resins has been studied in order to alleviate the disadvantages of the resins. The most effective way to improve the toughness is to introduce a second phase into the epoxy resin as a toughening agent.…”
mentioning
confidence: 99%
“…The studies about the chemical structural modification of epoxy resins have recently attracted much attention in attempts to enhance fracture toughness, T g , and thermal properties simultaneously . Kaji et al .…”
Section: Introductionmentioning
confidence: 99%
“…found that the incorporation of symmetric rigid chain segments, such as 4,4‐biphenylene or 2,6‐naphthylene moieties, into the molecular backbone could effectively improve fracture toughness, T g and heat‐resistant properties. A trifunctional epoxy resin containing oxyphenylene unit, triglycidyl of 4‐(4‐aminophenoxy)phenol (TGAPP) has been prepared, the toughness and tensile strength of corresponding cured resin increased obviously, while the heat resistance properties and flexural strength remained largely the same . A tetraglycidyl 1,4′‐bis(4‐amine‐phenoxy)benzene (TGBAPB) with an ether linkage was synthesized to improve the toughness of DGEBA .…”
Section: Introductionmentioning
confidence: 99%